The extent of small fibre sensory neuropathy in diabetics with plantar foot ulceration. - Ali, Z (1989)
Thresholds for cutaneous warming and cooling stimuli were measured in 20 diabetics with neuropathic foot ulcers. All patients had a profound disturbance of sensory perception in the ulcerated foot with complete loss of perception of warming; thresholds for vibration and cooling were highly abnormal in all but two patients. Measurements of thermal threshold were made on both feet in 10 patients: warming was lost bilaterally in all, and cooling was bilaterally absent in six. There was no clear pattern of sensory loss in those diabetics with unilateral foot ulceration to suggest that sensory impairment was the determining factor for the development of a plantar ulcer. Measurements of thermal thresholds were made at additional sites in 13 patients and although the most marked abnormalities of sensation were always found in the feet, in some severe neuropaths, abnormal thresholds on the hand and even the face were demonstrated. Thresholds for warming were invariably more abnormal than thresholds for cooling. The diabetics with neuropathic ulceration in this study all had severe generalised peripheral nerve disease involving large myelinated as well as both small myelinated and unmyelinated sensory fibres. The quantitative evidence on the distribution of sensory loss for thermal sensations supports the hypothesis that the neuropathic process affecting the small myelinated and unmyelinated fibres is length dependent.